Dekonstruksi dalam Novel Azab Dan Sengsara Karya Merari Siregar - Ridwan; Asriadi (Hasta Wiyata, 2025)
This research discusses Derrida's deconstruction theory which focuses on texts that build new meanings and reinforce existing meanings. The object of this research uses a novel entitled "Azab and Sengsara" by Merari Siregar. The novel "Azab and Sengsara" is studied using Derrida's deconstruction theory with qualitative research methods sourced from literature review. The results of the research obtained are that there are new meanings and confirmation of meaning in the texts of the novel Azab and Sengsara, namely 1) Aminuddin's punishment for helping a friend, 2) Aminuddin's attitude of helping others, 3) Restriction of women's space by Sutan laying on his wife, 4) Strong disclosure of men's identity, 5) Women who were blessed by God to become men through the angel Gabriel, 6) Divorce became a common practice, 7) High belief in shamans, 8) Mariamin refused to have sexual relations with her husband, and 9) Women are bought to fulfill men's desires. This research then obtained results using Post-structuralism theory, namely the theory of deconstruction by Jacques Derrida.